Low‐dose pembrolizumab in the treatment of advanced non‐small cell lung cancer. Issue 1 (6th March 2021) - Low, Jia Li; Huang, Yiqing; Sooi, Kenneth; Ang, Yvonne; Chan, Zhi Yao; Spencer, Katie; Jeyasekharan, Anand Devaprasath; Sundar, Raghav; Goh, Boon Cher; Soo, Ross; Yong, Wei Peng
Abstract: A dose of 200 mg 3‐weekly of pembrolizumab was approved by the Food and Drug Administration (FDA) as treatment for advanced non‐small cell lung cancer (NSCLC) without oncogenic drivers. This is despite evidence showing no difference in efficacy with 2 mg/kg. Our study aimed to assess the efficacy of a lower fixed dose of 100 mg, which is closer to 2 mg/kg weight‐based dose in an average‐sized Asian patient. All patients receiving pembrolizumab for advanced NSCLC from January 2016 to March 2020 in National University Hospital, Singapore, were included in this retrospective observational study. The effect of pembrolizumab 100 mg (Pem100) vs 200 mg (Pem200) upon survival outcomes, toxicity and cost were examined. One hundred fourteen patients received pembrolizumab. Sixty‐five (57%) and 49 (43%) received Pem100 and Pem200, respectively. There was no difference in progression‐free survival (PFS) and overall survival (OS) between Pem100 vs Pem200 as a single agent (PFS: 6.8 vs 4.2 months, hazard ratio [HR] 0.72, 95% confidence interval [CI] 0.36‐1.46, P = .36; 9 month OS: 58% vs 63%, HR 1.08, 95% CI 0.48‐2.41, P = .86) and when combined with chemotherapy (9‐month PFS: 60% vs 50%, HR0.84, 95% CI 0.34‐2.08, P = .71; 9‐month OS: 85% vs 58%, HR 0.27, 95% CI 0.062‐1.20, P = .09). No significant difference in response rate or ≥G3 immune‐related toxicities between Pem100 and Pem200 was observed. A cost minimisation analysis evaluating the degree of cost savings related to drug costs estimated a within study cost saving of SGD4, 290, 912 and cost saving per patient of SGD39, 942 in the Pem100 group. A 100 mg of pembrolizumab appears to be effective with reduction in cost. A randomised trial should be done to investigate a lower dose of pembrolizumab. Abstract : What's new? Pembrolizumab, a monoclonal antibody directed against the PD‐1 receptor, has received FDA approval for the treatment of lung cancer at a fixed dose of 200 mg every 3 weeks. However, doses above 2 mg/kg show a lack of benefit, calling for further evaluation in Asian populations. This retrospective observational study demonstrates the efficacy of a lower fixed dose of pembrolizumab (100 mg every 3 weeks) compared with standard‐dose pembrolizumab. The results also confirm the clinical activity of pembrolizumab at a lower dose than 2 mg/kg every 3 weeks, which could provide considerable cost savings to patients and the health system.